PENGARUH PELUBANGAN PADA BADAN BALOK BETON BERTULANG TERHADAP KAPASITAS BEBAN LENTUR - Vera Agustriana Noorhidana; Eddy Purwanto (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
The purpose of this study is to analyze the behaviour of reinforced concrete beam with web opening. The variable of research is the location of web opening on a beam. There were no strengthening around the opening to represent situation of making an opening on existing beam. There were three reinforced concrete beams (150mmx270mmx3000mm) as spesimens, namely a beam without web opening (Code: BU), a beam with web opening which is located on the middle of span of beam (Code: BLLTP), and the other one is a beam with web opening which is located near the support (Code: BLGTP). Compressive strength of concrete was 20 MPa. The beamswere simply supported on 2700mm clear span, and subjected to at two points load were located 900mm from the support. The results were curve of load-deflection, curve of moment-curvature, and crack pattern. The maximum load of BU, BLLTP, and BLGTP were 3717kg, 3581kg, dan 3649kg respectively. The curve of load-deflection and moment-curvature showed that after first crack was happened, the curve of BLLTP and BLGTP were more ramps than curve of BU. The cracks were concentrated on around of openings start at lower load. The results showed that making the web opening without strengthening on existing beam has a little effect on the load capacity of beams (below 5%), but decrease the stiffness of beam significantly.